The realization of the detailed local plans in urban areas in Turkey: a model - S. Sence Turk (European Regional Science Association (ERSA), 2002)
The main objective of the realization of local physical plan in urban areas is to constitute the healthy urban structure, to provide land development and to regulate the use of private and public land for public interest. The other important objective is to prevent sprawl of city and chaotic growth. The realization of local physical plan is a process which it express the change in an urban area from irregular plots of rural land to urban plots having infrastructure according to local physical plans. The municipalities are responsible for the realization of local physical urban plans in Turkey. There is not any sufficient research related to realization of local physical plans in urban spaces throughout the Turkey. The purpose of this study is to investigate whether there is a relationship between the realization rate of local physical plans and population, population growth rate, socio-economic index, the number of technical personnel, some dummy variables. For this research, a sample survey method is used and 468 questionnaires are completed by Planning Office of the municipalities of urban areas in Turkey. In this model, the index of realization local physical plan are used as a dependent variable and population, population growth rate, global density in urban areas according to detailed plans, adequacy of budgets, socio-economic index, the number of personnel, Multiple Regression Model is utilized for Turkey. The results of the paper can be used to identify the problems concerning the realization of local physical plans and to suggest solutions to these problems based on existing legislation in Turkey in international context.
Keywords: 330